Problematika Non-Linguistik Siswa Dalam Berbicara Bahasa Inggris - Cut Intan Meutia; Fadhillah Wiandari; Ade Hilda Husaini (JURNAL PENA EDUKASI, 2020)
Abstract: This study aims to determine the non-linguistic problems faced by students of the English Department in learning to speak and the steps that must be taken to overcome non-linguistic problems faced by students. This research uses a qualitative approach. Research participants were fifth-semester students of the English Department. The instruments used in this study were semi-structured interviews and closed questionnaires. Data collection was carried out through observation, interviews, and questionnaires. The collected data were analyzed using a qualitative data analysis approach. The analysis was carried out in three steps; data reduction, data presentation, and concluding. The results showed that students experienced difficulties in practicing speaking activities due to non-linguistic factors such as anxiety, nervousness, shame, and self-confidence. Other factors, such as motivation, teaching methods, and teaching materials, also hinder students in learning to speak. However, not all students experience non-linguistic problems in learning to speak. Keywords: non-linguistic; speaking  Abstrak: Penelitian ini bertujuan untuk mengetahui permasalahan nonlinguistik yang dihadapi mahasiswa Jurusan Bahasa Inggris dalam pembelajaran berbicara dan langkah-langkah yang harus diambil untuk mengatasi permasalahan nonlinguistik yang dihadapi mahasiswa. Penelitian ini menggunakan pendekatan kualitatif. Partisipan penelitian adalah mahasiswa semester lima Jurusan Bahasa Inggris. Instrumen yang digunakan dalam penelitian ini adalah wawancara semi terstruktur dan kuesioner tertutup. Pengumpulan data dilakukan melalui observasi, wawancara dan kuesioner. Data yang terkumpul dianalisis dengan menggunakan pendekatan analisis data kualitatif. Analisis dilakukan melalui tiga langkah; reduksi data, penyajian data dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa siswa mengalami kesulitan dalam mempraktikkan kegiatan berbicara karena faktor non kebahasaan seperti kecemasan, gugup, malu dan percaya diri. Faktor lain seperti motivasi, metode pengajaran dan bahan ajar juga menjadi penghambat siswa dalam belajar berbicara. Namun, tidak semua siswa mengalami masalah non-linguistik dalam pembelajaran berbicara. Kata kunci: berbicara; non-linguistik